The Role of Family Disintegration in Piracy of Electronic Games “A Field Study” - Mahmoud Awad, Heba Atef El-Sayed (International Journal of Criminology and Sociology, 2021)
Purpose: Recognizing the technological effects of family disintegration. Method: Human field: a sample of the dangerous electronic games players, including "4" players who are still alive, and "5" players who committed suicide. Methods and Tools: The Case study method, Ethnographic method, Descriptive approach, and Interview. The research type is Analytic, and the theoretical framework is Postmodernism Theory. Originality: The researcher tries to provide a comprehensive view of how electronic games piracy on their players and pushes them to suicide, in the presence of the family disintegration element. Findings: family disintegration was the main reason for children’s addiction to electronic games. Thus, electronic games were like escaping from reality and living in imagination, and spending free time. Also, electronic games were a means that absorbed the negative charge and feelings of anger among the children instead of the family. There are many types of piracy on players: (programming for the mind, charging with negative thoughts, threatening to kill parents, an emotional challenge to the teenager, blackmail and intimidation, or with talismans). Conclusion: a person can control another, to the extent that this other person allows this person to control him. Do not allow a game administrator to control you, activate Cybersecurity.